PENGARUH LATIHAN FOOTWORK TERHADAP PUKULAN DROPSHOT DALAM PERMAINAN BULUTANGKIS - Muhammad Salahuddin (Jurnal Panrita, 2021)
This study focuses on the problem of PJKR Students at Unismuh of Luwuk Banggai when participating in a badminton championship. Their average performance shows that they rarely gave dropshots during the match. In fact, they almost never did this because of the lack of training given that they are doubtful to shoot. The purpose of this study was to determine the effect of footwork training on dropshots during badminton matchesq for PJKR Unismuh Luwuk students and the research method used for this study was one pretest-posttest group. Based on the results of the data analysis of the drop shot skills in badminton game with a different test (paired t-test) between the initial test and the final test in the experimental group of footwork exercises, the t-count = 12.310 (α 0.05 > sig = 0.000) with the mean score of the initial test was 30.75 and the final test result was 38.83. Thus, there is an increase of 8.08 point. This one indicates a significant effect of footwork training on drop shot skills in badminton. The results of the data analysis of the accuracy of the drop shot in the badminton game with a different test (paired t-test) between the initial test and the final test in the control group obtained t count = 1.567 (67 0.05 < sig = 0.145) while in the control group shows the score at 0.17 and the final test result is 30.92, thus there is an increase of 0.75. Thus, it can be stated that the experimental group has footwork exercises and has a significant effect on improving drop shot skills in badminton games for PJKR Unismuh Luwuk Banggai students.